A Holistic Conception of Sustainable Banking: Adding Value with Fuzzy Cognitive Mapping - Carlucci, D.; Ferreira, F.; Schiuma, G.; Jalali, M.; António, N. (2015 BAI International Conference, 2015)
Integrating sustainability into the banking activity is an increasingly necessary but extremely challenging issue currently facing financial institutions. It is therefore becoming ever more important to understand the key determinants of sustainable banking and how they inter-relate with each other. As such, this research aims to build a cognitive map – a fuzzy cognitive map (FCM) in particular – to model, and dynamically analyze and test the reciprocal influence of key factors underlying sustainable banking. FCMs have been shown to be particularly useful for handling complex decision problems characterized by lack of information or unavailable data. They constitute a methodological framework that allows for a reduction of omitted determinants – in this case, with regard to sustainable banking; and are typically able to provide a greater understanding of the relationships between such determinants. We know of no previous work using this methodology in this area; and believe this first effort in the application of cognitive mapping techniques to the identification of the key determinants of sustainable banking will be an important contribution to both theory and practice. We anticipate implications and practical applications for both bank managers and policymakers aiming to increase the efficiency of their decision making in the context of sustainable banking.